Enhancing students’ motivation to learn English through reading English novels in language classrooms - Ni Made Parmita Darma Astuti; I Putu Yoga Laksana; Majid Wajdi; Rodolfo P. Dizon Jr; Zanyar Nathir Ghafar; Omar Mohammad-Ameen Ahmad Hazaymeh; Md. Kamrul Hasan (Yayasan Mitra Persada Nusantara, 2026)
This study aims to explore how reading English novels enhances students’ motivation to learn the English language. A qualitative and quantitative mixed-method approach was employed, involving senior students from English departments who engaged in extensive novel reading programs. Data were collected through pre- and post-assessments, questionnaires, and observational notes to analyse changes in motivation, vocabulary acquisition, and language skills development. Statistical analysis revealed significant improvements in students’ motivation, vocabulary size, and overall language proficiency after engaging with novels. The findings suggest that novels serve as flexible, engaging learning tools that cater to diverse learning styles while fostering creativity, cultural understanding, and communication skills. Incorporating novels into English curricula is recommended to boost student motivation and enhance language learning outcomes effectively.